Government statement on the report of the administrative enquiry on the circumstances leading to the authorization and disburesment of N395,721.15 to the Nigerian Technical Company (NITECO), Apapa on the 7th June, 1974 (Nigeria : Nigeria, 1974)
This is an official document No. 5 of 1974 from the South-Eastern State of Nigeria on the authorization and disbursement of N395,721.15 to the Nigerian Technical Company (NITECO), Apapa on 7 June 1974 arising from the discovery of financial irregularity.
This is an official document No. 5 of 1974 from the South-Eastern State of Nigeria.
nmn, 14/03/19
Loans
Keywords: Administrative enquiry; Disbursement; Nigeria technical company (NITECO)